2015
DOI: 10.1016/j.janxdis.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of change during group metacognitive therapy for repetitive negative thinking in primary and non-primary generalized anxiety disorder

Abstract: Repetitive negative thinking (RNT) is a transdiagnostic process that serves to maintain emotional disorders. Metacognitive theory suggests that positive and negative metacognitive beliefs guide the selection of RNT as a coping strategy which, in turn, increases psychological distress. The aim of this study was to test the indirect effect of metacognitive beliefs on psychological distress via RNT. Patients (N=52) with primary and non-primary generalized anxiety disorder attended a brief, six-week group metacogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The clinically significant results obtained for the group MCT appeared to be better or equal to the group CBT cohort and those typically found in RCTs of CBT for OCD, especially given the low attrition rate in a group for whom 76.8% were prescribed medication. The results of the group MCT also contribute to a growing body of empirical evidence attesting to the effectiveness of this intervention in group formats for generalized anxiety disorder in children (Esbjørn et al, 2018) and adults (Van der Heiden et al, 2013; McEvoy et al, 2015), depression (Dammen et al, 2015), antidepressant and CBT-resistant depression (Papageorgiou and Wells, 2015), and transdiagnostic patient samples (Capobianco et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The clinically significant results obtained for the group MCT appeared to be better or equal to the group CBT cohort and those typically found in RCTs of CBT for OCD, especially given the low attrition rate in a group for whom 76.8% were prescribed medication. The results of the group MCT also contribute to a growing body of empirical evidence attesting to the effectiveness of this intervention in group formats for generalized anxiety disorder in children (Esbjørn et al, 2018) and adults (Van der Heiden et al, 2013; McEvoy et al, 2015), depression (Dammen et al, 2015), antidepressant and CBT-resistant depression (Papageorgiou and Wells, 2015), and transdiagnostic patient samples (Capobianco et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…This highlights the importance of investigating the efficacy of therapeutic programs targeting Repetitive Negative Thinking for students who have high levels of Academic Burnout (particularly that characterised by Exhaustion) and high levels of Perfectionistic Concerns. Repetitive Negative Thinking can be reduced through targeted interventions ( Watkins, 2018 ), or through metacognitive therapy, and this is associated with improvements in several measures of psychological distress ( Johnson et al., 2017 ; McEvoy et al, 2015 ). The importance of Repetitive Negative Thinking as a treatment for burnout would critically depend upon whether any modification of a student’s Repetitive Negative Thinking is also associated with changes in their experiences of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, higher levels of Perfectionistic Strivings are associated with less Academic Burnout. Given that there are treatment programs which can effectively reduce both Perfectionistic Concerns and Repetitive Negative Thinking ( McEvoy et al, 2015 ; Rozental et al, 2017 ), future research should focus on understanding the extent to which these programs can alleviate Academic Burnout in university students.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by sessions 3 and 6 some participants experienced an increase in MCQ‐C Pos scores. For example, the scores of participants E and H indicated reliable and clinically significant deterioration (see Figure and Table ), which subsequently reduced to subclinical levels for participant E but not for participant H. Previous research on RNT and metacognitions has shown that the influence of positive metacognitive beliefs appears to be less essential to treatment outcome than that of negative metacognitive beliefs, at least in the short term (McEvoy, Erceg‐Hurn, Anderson, Campbell, & Nathan, ). Scores on the MCQ‐C Neg showed a clearer pattern of change, with eight of the participants' scores in the clinical range at pretreatment and five out of nine showing improvement or recovery by the 3‐month follow‐up.…”
Section: Discussionmentioning
confidence: 85%